2020
DOI: 10.2174/0929867326666191113113110
|View full text |Cite
|
Sign up to set email alerts
|

The CXCL12-CXCR4 Signaling Axis Plays a Key Role in Cancer Metastasis and is a Potential Target for Developing Novel Therapeutics against Metastatic Cancer

Abstract: Metastasis is the main cause of death in cancer patients; there is currently no effective treatment for cancer metastasis. This is primarily due to our insufficient understanding of the metastatic mechanisms in cancer. An increasing number of studies have shown that the C-X-C motif chemokine ligand 12 (CXCL12) is overexpressed in various tissues and organs. It is a key niche factor that nurtures the pre-metastatic niches (tumorigenic soil) and recruits tumor cells (oncogenic “seeds”) to these niches, thereby f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 168 publications
0
25
0
Order By: Relevance
“…Several studies have demonstrated that the CXCR4/CXCL12 axis plays a crucial role in organ-specific metastasis formation [28][29][30]. CXCL12, a ligand for CXCR4, is abundantly produced by neighboring stromal cells and activation of CXCR4-expressing cancer cells by CXCL12 leads to enhanced chemotaxis, trans-endothelial migration, and invasion.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated that the CXCR4/CXCL12 axis plays a crucial role in organ-specific metastasis formation [28][29][30]. CXCL12, a ligand for CXCR4, is abundantly produced by neighboring stromal cells and activation of CXCR4-expressing cancer cells by CXCL12 leads to enhanced chemotaxis, trans-endothelial migration, and invasion.…”
Section: Discussionmentioning
confidence: 99%
“…This microenvironment is known as the pre‐metastatic niche. Indeed, CXCL12/CXCR4 signaling contributes to the development of the pre‐metastatic niche and disruption of CXCL12/CXCR4 signaling is effective in inhibiting metastasis 83,87‐89 …”
Section: Endothelial Cellsmentioning
confidence: 99%
“…The CXCL12‐CXCR4 signaling regulates organogenesis, hematopoiesis, and angiogenesis during gestational development and lymphocyte development 100‐103 as well as the typical chemokine functions for the recruitment of immune cells such as dendritic cells and lymphocytes 104,105 . The CXCL12‐CXCR4 axis is well known to promote cancer development and metastasis by enhancing angiogenesis, cell migration, and EMT 106‐108 . Thus, CXCL14 inhibition of CXCL12 binding to CXCR4 may be a pertinent mechanism of CXCL14‐mediated tumor suppression.…”
Section: Cxcl14 Candidate Receptorsmentioning
confidence: 99%